Developing applications using model-driven design environments - Balasubramanian, K.; Gokhale, A.; Karsai, G.; Sztipanovits, J.; Neema, S. (Computer (Long Beach, Calif.), 2006)
Historically, software development methodologies have focused more on improving tools for system development than on developing tools that assist with system composition and integration. Component-based middleware like Enterprise Java-Beans (EJB), Microsoft .NET, and the CORBA Component Model (CCM) have helped improve software reusability through component abstraction. However, as developers have adopted these commercial off-the-shelf technologies, a wide gap has emerged between the availability and sophistication of standard software development tools like compilers and debuggers, and the tools that developers use to compose, analyze, and test a complete system or system of systems. As a result, developers continue to accomplish system integration using ad hoc methods without the support of automated tools. Model-driven development is an emerging paradigm that solves numerous problems associated with the composition and integration of large-scale systems while leveraging advances in software development technologies such as component-based middleware. MDD elevates software development to a higher level of abstraction than is possible with third-generation programming languages.